Pivoting during a pandemic: a case study of a Samoan NGO. Issue 8 (17th November 2021) - Tierney Lemisio, Annika; Boodoosingh, Ramona; Utumapu, Mata'afa Fa'atino
ABSTRACT: The COVID-19 pandemic has disproportionately affected persons with disabilities in ways that include unemployment, inability to adhere to public health measures, and access to health information. The needs of this vulnerable population have been met to a large extent by NGOs in developing countries. With evolving needs during the pandemic, so too have NGOs had to adapt, by pivoting their areas of focus and delivery in a short space of time. In this short report, the authors will discuss how Nuanua O Le Alofa, a Samoan NGO which supports persons with disabilities shifted its area of focus from advocacy to operational service delivery.